CASE C-648/18 HIDROELECTRICA, CJEU – A PREDICTABLE DECISION - Ionela-Alina ZORZOANĂ (Challenges of the Knowledge Society, 2021)
This study proposes a post factum analysis (or rather a final conclusion) of the solution ruled in Case C-648 Hidroelectrica, a case that came before the Court of Justice of the European Union1 , as a preliminary question referred to by the Bucharest Tribunal , as a national court2 . The case was of real interest in the context in which the preliminary question concerned the interpretation given by a national authority to a rule of domestic law, and not to a rule of European law. Unfortunately, the solution ruled by the CJEU, predictable as of the time of establishing the oral phase in the case, was no surprise, representing a faithful copy of Hidroelectrica's request and adhered to without any reservation by the European Commission. This study shall be a critical analysis (perhaps too critical in certain places) of the reasoning of the CJEU judgment versus the point of view expressed by the European Commission and the conclusions of the Advocate General of the Court, true defenders of the operator in this case. Last but not least, an important part shall be devoted to the previous practice of the CJEU in terms of the inadmissibility of the preliminary questions and a sudden change thereof, which leaves deep question marks as to the status of the Court, independent otherwise (or at least so it should be). In the final part, before the conclusions, we shall also refer to the applicability of the principle of proportionality, so much invoked in the CJEU Judgment.